XR training and gameplay 6DoF mobility dataset - De Kunst, Sam; Marinšek Alexander; Callebaut, Gilles; De Strycker, Lieven; Van der Perre, Liesbet (Zenodo, 2023)
User mobility in extended reality (XR) can have a major impact on millimeter-wave (mmWave) links and may require dedicated mitigation strategies to ensure reliable connections and avoid service outages. The available prior art has predominantly focused on XR applications with constrained user mobility and limited impact on mmWave channels. We have performed dedicated experiments to extend the characterisation of relevant future XR use cases featuring a high degree of user mobility. To this end, we have carried out a tailor-made measurement campaign. For a description, for analysis results, and for citing the dataset, view [coming soon]